1997
DOI: 10.1093/gerona/52a.6.b300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Calorie Intake on Intestinal Nutrient Uptake and Transporter mRNA Levels in Aged Mice

Abstract: In aged, chronically calorie-restricted (CR) mice, intestinal nutrient uptake is significantly higher than in same-age ad libitum controls. Can this chronic restriction-induced enhancement of uptake be reversed by ad libitum feeding? We addressed this question by switching 32-mo-old chronically CR mice to ad libitum feeding for 4 wk (CRAL). Intestinal transport rate and total intestinal absorptive capacity for D-sugars and several nonessential L-amino acids decreased significantly in CRAL mice. In contrast, sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Intestinal nutrient uptake in CR animals is significantly higher for D-sugars, L amino acids and L-glucose than in same-age AL animals (Casirola et al, 1997). Switching CR mice to AL feeding for 3 days had no effect on intestinal nutrient transport, indicating that the negative effects of AL require duration longer than the 3 days lifetime of most enterocytes.…”
Section: Alimentary Tractmentioning
confidence: 83%
See 1 more Smart Citation
“…Intestinal nutrient uptake in CR animals is significantly higher for D-sugars, L amino acids and L-glucose than in same-age AL animals (Casirola et al, 1997). Switching CR mice to AL feeding for 3 days had no effect on intestinal nutrient transport, indicating that the negative effects of AL require duration longer than the 3 days lifetime of most enterocytes.…”
Section: Alimentary Tractmentioning
confidence: 83%
“…Switching CR mice to AL feeding for 3 days had no effect on intestinal nutrient transport, indicating that the negative effects of AL require duration longer than the 3 days lifetime of most enterocytes. However, enhanced intestinal nutrient uptake under CR mice can be reversed by AL feeding for a month (Casirola et al, 1997). CR at 40% started at age 14 weeks enhances insulin stimulation of the glucose transport system independent of changes in basal glucose transport or muscle GLUT4 levels.…”
Section: Alimentary Tractmentioning
confidence: 93%
“…The small intestine regulates fructose absorption from dietary sources and, therefore, the availability of fructose to other tissues. It is also the organ system expressing the greatest amount of GLUT5 in human (13,20,47,79,81), rat (24, 35-38, 45, 72, 75, 84, 108, 112, 113, 139, 140, 147), mouse (22,33,83,107), rabbit (109), chicken (60), and horse (104). In cattle, GLUT5 expression in the intestine is significantly lower than in skeletal muscle (159), probably because this species is a foregut fermenter, and it is possible that fructose-like cellulose and other carbohydrate products are fermented in the stomach and little sugar reaches the intestinal lumen.…”
Section: Physiology and Functionmentioning
confidence: 99%
“…To our knowledge, studies of genetic interventions that extend lifespan in mammalian models have not reported associated or required changes in intestinal biology. However, mice subjected to caloric restriction, a dietary intervention that robustly extends lifespan in a number of diverse invertebrates and mammals, were observed to maintain an intestinal absorption capacity for sugars and amino acids nearly twice as high as that of control mice, thereby associating enhanced and/or maintained intestinal function with lifespan extension (Casirola et al, 1997). Whether or not such an association is causal remains to be deciphered.…”
Section: Is the Intestine Significant In Mammalian Lifespan Extension?mentioning
confidence: 99%